Expedition Lepanthes (Orchidaceae) of Colombia: discovery of six new species and observations on a curious case of flower polymorphism - Arias, Tatiana; Moreno, Juan Sebastián; Restrepo, Eugenio; Alegría-Valencia, Melisa; Cadavid-Morales, David Emilio; Alarcón-Vinasco, Sergio Fernando; Davila, Camila; Zuluaga, Alejandro (Phytotaxa, 2025)
Field exploration across five Andean regions of Colombia resulted in the identification of 102 species in Lepanthes, documented through herbarium specimens, including spirit collections, and DNA voucher samples. Subsequent taxonomic analysis and further exploration allowed us to identify six new species, which are formally described here. We report an unprecedented case of flower polymorphism, where individuals at two distinct sites exhibited both flower morphologies previously recognized as separate species, Lepanthes silverstonei and L. licrophora. Based on these observations, we propose the synonymization of L. licrophora under the older name, L. silverstonei. This study significantly contributes to the understanding of Colombian Lepanthes diversity and establishes a foundation for future taxonomic, ecological, and conservation efforts.